Proposta de método para avaliação do desempenho térmico de residências unifamiliares em clima quente e úmido - Oliveira, Alexandre Gomes de (2006)
Nowadays, evaluation methods to measure thermal performance of buildings have been developed in order to improve thermal comfort in buildings and reduce the use of energy with active cooling and heating systems. However, in developed countries, the criteria used in rating systems to asses the thermal and energy performance of buildings have demonstrated some limitations when applied to naturally ventilated building in tropical climates. The present research has as its main objective to propose a method to evaluate the thermal performance of low-rise residential buildings in warm humid climates, through computational simulation. The method was developed in order to conceive a suitable rating system for the athermal performance assessment of such buildings using as criteria the indoor air temperature and a thermal comfort adaptive model. The research made use of the software VisualDOE 4.1 in two simulations runs of a base case modeled for two basic types of occupancies: living room and bedroom. In the first simulation run, sensitive analyses were made to identify the variables with the higher impact over the cases´ thermal performance. Besides that, the results also allowed the formulation of design recommendations to warm humid climates toward an improvement on the thermal performance of residential building in similar situations. The results of the second simulation run was used to identify the named Thermal Performance Spectrum (TPS) of both occupancies types, which reflect the variations on the thermal performance considering the local climate, building typology, chosen construction material and studied occupancies. This analysis generates an index named IDTR Thermal Performance Resultant Index, which was configured as a thermal performance rating system. It correlates the thermal performance with the number of hours that the indoor air temperature was on each of the six thermal comfort bands pre-defined that received weights to measure the discomfort intensity. The use of this rating system showed to be appropriated when used in one of the simulated cases, presenting advantages in relation to other evaluation methods and becoming a tool for the understanding of building thermal behavior